Trace [large type] - Mayor, Archer (Mayor, Archer. Joe Gunther novel., 2017)
"The Vermont Bureau of Investigation (VBI) is suddenly swamped. The Bureau has been pulled onto three cases at the same time, while unexpectedly, VBI head Joe Gunther has to take time off to care for his ailing mother."--Book jacket.